Recovery of gold and silver from minerals by heap leaching - Azañero Ortíz, Ángel (2001)
Heap leaching is a very economical process to metallurgically treat low grade minerals in precious metals, this treatment method received a strong boost in the mid-70s of the previous century, when gold reached quotes of up to US $ 600 / ounce in 1980, the reuse of activated carbon is implemented and minerals with a high content of fines are processed through agglomeration.